2021
DOI: 10.1007/s11657-021-00901-0
|View full text |Cite
|
Sign up to set email alerts
|

The serum 25(OH)D level and hand grip strength for fall risk assessment among osteoporotic elderly Japanese women

Abstract: Summary We investigated the relationship between serum 25(OH)D levels, grip strength, and fall score in elderly osteoporotic women for fall risk assessment. Both low serum 25(OH)D and low grip strength were independently associated with increased fall risk. The serum 25(OH)D cutoff specific to increased fall risk was 14 mg/dL (35 nmol/L). Purpose This study aimed to establish a cutoff value of serum 25-hydroxyvitamin D (25(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Malnutrition is frequent in the older and there is an evidence that the supplementation of essential amino acid can prevent the older from sarcopenia (16,17). Meanwhile, low 25(OH)VD levels have been confirmed to lead to loss of muscle mass and grip strength through the reduction in II type muscle fiber synthesis identified as fast twitch, which was also consistent with our findings (18,19). Several studies have already showed that 25(OH)VD could induce muscle cells proliferation, differentiation, and regulate muscle regeneration initiation (20,21).…”
Section: Discussionsupporting
confidence: 90%
“…Malnutrition is frequent in the older and there is an evidence that the supplementation of essential amino acid can prevent the older from sarcopenia (16,17). Meanwhile, low 25(OH)VD levels have been confirmed to lead to loss of muscle mass and grip strength through the reduction in II type muscle fiber synthesis identified as fast twitch, which was also consistent with our findings (18,19). Several studies have already showed that 25(OH)VD could induce muscle cells proliferation, differentiation, and regulate muscle regeneration initiation (20,21).…”
Section: Discussionsupporting
confidence: 90%
“…38 Hand grip strength is strongly associated with overall muscle strength and is a valuable indicator of well-being, functional status, and frailty and can be a predictor of falls and postsurgical complications in older adults. 38,39 The pathophysiology of frailty is related to insulin resistance. 40 Therefore, the frailty of participants in the two groups was compared using hand grip strength but no difference was observed.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the fall risk, a fall score was used, with five data items based on activities of daily living. 31 Scores for each item were calculated based on odds ratios; those with a score of 6 points or more were considered at high risk for falls 20,31 : (1) have fallen in the past year, (2) think their walking speed has slowed down recently, (3) use a cane, (4) think their back has rounded recently, (5) take 5 or more medications; the score for each item was calculated based on odds ratio. Each item was scored differently; if the participant answered Yes, 5 points were allocated to the first question and 2 points each were allocated for questions 2-5.…”
Section: Assessment Of Risk Of Fallmentioning
confidence: 99%